The Influence of Palmatine Isolated from Berberis sibirica Radix on Pentylenetetrazole-Induced Seizures in Zebrafish - Kinga Gawel; Wirginia Kukula-Koch; Dorota Nieoczym; Katarzyna Stepnik; Wietske van der Ent; Nancy Saana Banono; Dominik Tarabasz; Waldemar A. Turski; Camila V. Esguerra (Cells, 2020)
Palmatine (PALM) and berberine (BERB) are widely identified isoquinoline alkaloids among the representatives of the Berberidaceae botanical family. The antiseizure activity of BERB was shown previously in experimental epilepsy models. We assessed the effect of PALM in a pentylenetetrazole (PTZ)-induced seizure assay in zebrafish, with BERB as an active reference compound. Both alkaloids were isolated from the methanolic root extract of Berberis sibirica by counter-current chromatography, and their ability to cross the blood–brain barrier was determined via quantitative structure–activity relationship assay. PALM exerted antiseizure activity, as confirmed by electroencephalographic analysis, and decreased c-fos and bdnf levels in PTZ-treated larvae. In a behavioral assay, PALM dose-dependently decreased PTZ-induced hyperlocomotion. The combination of PALM and BERB in ED16 doses revealed hyperadditive activity towards PTZ-induced hyperlocomotion. Notably, we have indicated that both alkaloids may exert their anticonvulsant activity through different mechanisms of action. Additionally, the combination of both alkaloids in a 1:2.17 ratio (PALM: BERB) mimicked the activity of the pure extract, which indicates that these two active compounds are responsible for its anticonvulsive activity. In conclusion, our study reveals for the first time the anticonvulsant activity of PALM and suggests the combination of PALM and BERB may have higher therapeutic value than separate usage of these compounds.